METHODS ELABORATION ON DETECTION OF SOME ATYPICAL NEUROLYTIC AGENTS FOR CHEMICAL AND TOXICOLOGICAL ANALYSIS - I. P. Remezova; D. S. Lazaryan; T. I. Maksimenko; D. Yu. Sanzhieva; A. Yu. Rybasova (Фармация и фармакология (Пятигорск))
It is necessary to elaborate methods of atypical neuroleptic agents detection as individual substances and in different combinations as well for diagnosis of poisoning by some of them: clozapine, risperidone, sertindole, olanzapine, aripiprazole. The purpose of this work is methods elaboration of detection of clozapine, risperidone, sertindole, olanzapine, aripiprazole, haloperidol, oxazepam, carbamazapine using TLC, HPLC and UV spectrophotometry methods. During this work we used tablet forms of clozapine, risperidone, sertindole, olanzapine, aripiprazole. It is possible to use solution systems like ethanol-water-25% ammonia solution (8:1:1), toluolacetone-ethanol-25% ammonia solution (45:45:7.5:2.5), dioxan-chloroform-acetone-25% ammonia solution (47.5:45:5:2.5) for preliminary examination of atypical neuroleptic agents under study in combination with typical neuroleptics and tranquilizers with undirected analysis (general screening). System of solvents ethyl-acetate-chloroform-25% ammonia solution (85:10:5) is recommended to use for individual screening of risperidone, sertindole, olanzapine, haloperidol, benzol-ethanol-25% ammonia solution (50:10:0.5) system to use for clozapine, sertindole, olanzapine. Ethanol-25% ammonia solution (100:1.5) system is reasonable to use for chromatographic clearance of extracts from biological substances under study. We recommend using HPLC method and UV spectrophotometry for carrying out of a principal examination of clozapine, risperidone, sertindole, olanzapine and aripiprazole in case one of the substances under study is determined in the object.